The empire of night [compact disc, unabridged] - Butler, Robert Olen (Butler, Robert Olen. Christopher Marlowe Cobb thriller, 2014)
It is 1917, and the United States is still wavering on the brink of war. At an elite intelligence meeting, Kit's handlers pair him up with someone he would never have expected-his mother. There's a German mole somewhere in the British government, and the most likely suspect happens to be a diehard fan of a famous American theater actress. Disguised as a German-American reporter, Kit follows his mother and her escort Sir Albert Stockman from London into the lion's den of Berlin.